Contributions and challenges of preceptorship in Nursing Residency Programs (Research, Society and Development, 2021)
Objective: To identify from the search in the scientific literature, the contributions and challenges experienced by nurse preceptors of Nursing Residency Programs. Method: Study of scientific literature review, carried out in the databases of Online System for Search and Analysis of Medical Literature, Nursing Database, Latin American and Caribbean Literature in Health Sciences and Scientific Electronic Library Online, published between 2010 and 2020 and in Portuguese, English or Spanish. The results were presented based on the analysis and synthesis of the evidence obtained, discussing them in the light of the theoretical framework. Results: The final sample of the study consisted of eight articles in English and Portuguese, predominantly Brazilian, qualitative and with year of publication in 2013, pointing out challenges to preceptorship in Nursing Residency Programs shortages related to qualification, skills and professional recognition and as a contribution to active participation in the training of students and constant search for new knowledge for theoretical and practical domain. Final considerations: Changes are necessary to stimulate professional satisfaction and fulfillment, incentive to pedagogical qualification and recognition of the importance of the preceptor's role in the training of residents are necessary.